2013
DOI: 10.3329/jueb.v2i0.16326
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Pesticide Exposure on Paddy Farmers’ Health

Abstract: Effects of pesticide exposure on farmer’s health are conducted mostly in developed countries, which is rare in least developed countries like Bangladesh. Here farmers had less guidance and instruction about the preventive measures to protect themselves and environment. This work was studied to assess the impacts of pesticide exposure on the paddy farmer’s health in two different Upazilas of Manikganj, Bangladesh. The study was conducted as cross-sectional study with quantitative and qualitative components. Fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…In the South Asian region, where agriculture is a key determinant of economy and livelihood, the magnitude of risk of pesticide exposure is anticipated to be even higher due to a lack of resources, awareness, and education materials on PPE. A study of over 500 farmers in rural Bangladesh reported a high proportion of farmers using toxic pesticides and almost 70% did not use any PPE during application [1]. Data of this Bangladesh study was consistent with other agricultural health studies conducted elsewhere in Asia.…”
Section: Introductionsupporting
confidence: 85%
“…In the South Asian region, where agriculture is a key determinant of economy and livelihood, the magnitude of risk of pesticide exposure is anticipated to be even higher due to a lack of resources, awareness, and education materials on PPE. A study of over 500 farmers in rural Bangladesh reported a high proportion of farmers using toxic pesticides and almost 70% did not use any PPE during application [1]. Data of this Bangladesh study was consistent with other agricultural health studies conducted elsewhere in Asia.…”
Section: Introductionsupporting
confidence: 85%
“…Rice, wheat, jute, potato, sugarcane, vegetables, and tea are the main crops cultivated in the country (Chowdhury et al., 2013). The paddy fields consume 70% of the total pesticides (Bhattacharjee, 2013). In Bangladesh, insecticides are largely used than herbicides, fungicides, acaricides, and rodenticides.…”
Section: Main Textmentioning
confidence: 99%
“…Studies found that pesticide residues can cause nausea, vomiting, blurred vision, coma, difficulty in breathing, deficit hyperactivity disorder in the human body (Rauh et al., 2006). A study found that 26.3%, 24.4% and 18.8% farmers of their study reported excessive sweating, burning eyes and fatigue respectively due to occupational exposure of pesticides (Bhattacharjee, 2013). A daily newspaper published that 11 children were died by diseases which were provoked by pesticides at Dinajpur medical college hospital between May 30 to June 20 (Roy and Karmakar, 2015).…”
Section: Main Textmentioning
confidence: 99%
“…Pesticide chemicals (insecticides) may induce oxidative stress leading to the generation of free radicals and alterations in antioxidants or free radical scavenging enzyme systems (Duzguner and Erdogan, 2010). However, the impact of this indiscriminate use of pesticide are regularly monitored and controlled in a developed country but hardly seen in a developing country like Bangladesh (Bhattacharjee et al, 2013). Besides this, there is an alarming number of acute and chronic health effects because of exposure to those pesticides are being recorded (Chitra et al, 2006).…”
Section: Introductionmentioning
confidence: 99%